Kandungan Fosfor dan pH Tanah Akibat Pemupukan Nitrogen dan Fosfor pada Ultisols dan Inseptisols - Soni Isnaini (Jurnal Agrista, 2007)
Content of Soil Phosphorus and pH Caused by Nitrogen and Phosphorus Fertilizations on Ultisols and InceptisolsABSTRACT. The objective of this research were to study the effect on nitrogen (N) and phosphorus (P) fertilization on pH, content of soil P and dry weight of sunflowers (Heliantus annuus L.) on Ultisols and Inceptisols. The design of experiment used was a randomized completely block design arranged in factorial pattern with two factors. The first factor was N fertilizer (without N and 100 kg ha-1 N) and the second factor was P fertilizer (without P, 50, 100, and 150 kg ha-1 P). The result showed that the application P fertilizer several dosage was increasing soil pH, total soil P, and dry weight of sunflowers on Inceptisols and Ultisols. Available P was more strongly influenced by soil of order (Inceptisols was better than Ultisols) due to application of P fertilizer several dosage on 100 kg ha-1 N.